Antimetastatic and immunomodulatory potential of strobilanthes crispus subfraction and its specific major components in experimental breast cancer model - Baraya, Yusha'u Shu'aibu (2018)
Strobilanthes crispus (S. crispus), is a Malaysian herb locally known as ‗Pecah kaca‘ or ‗Jin batu‘ which have demonstrated potent anticancer effects in both in vitro and in vivo models. However, there is paucity of information on the inhibition of metastasis and immune activation potentials of S. crispus as part of its anticancer mechanism. Thus in this study, the antimetastatic and immunomodulatory activities of S. crispus subfraction (SCS) and its specific major constituents, lutein and β-sitosterol were investigated, particularly to unravel the underlying mechanisms involved, using in vitro and in vivo models of breast cancer. In the in vitro study, murine and human breast cancer cell (BCC) lines, 4T1 and MDA-MB-231, respectively, were treated with SCS and investigated for antimetastatic activity using cell proliferation, wound-healing and invasion assays. The results showed that SCS induced moderate cell growth arrest after 24h (100 μg/ml) and 48h (75 μg/ml) treatment of 4T1 and MDA-MB-231 BCC lines compared to the untreated control cells. SCS moderately inhibited metastasis independent of its cytotoxic effects due to inhibition of migration and invasion of cancer cells below the half maximal inhibitory concentration compared to the untreated control cells. In addition, flow cytometry was carried out to evaluate the expression of cell surface immune markers (CIITA, MHC I and MHC II) in 4T1 cells treated with SCS (50 μg/ml) for 24h, and the results showed considerable expression of all the tested proteins compared to the isotype control. The in vivo study evaluated the antimetastatic and immunomodulatory activities of SCS, lutein and β-sitosterol in 4T1-induced mouse mammary carcinoma model. Beginning from 2 mm tumor size, five each (n = 5) from tumor bearing mice (TM) were administered SCS (TM-S group), lutein (TM-L group) and β-sitosterol (TM-β group) by oral gavage daily for 30 days, and the response to treatment was assessed based on the outcome of the tumor growth parameters, as well as hematological and histomorphological analyses. The results demonstrated a few complete regression of primary tumor (20%) in TM-S (100 mg/kg/day) and partial tumor regression in the rest of TM-S, TM-L and TM-β (50 mg/kg/day), and without secondary tumor formation or tumor-associated lesions in the major organs of treated groups compared to the TM group. The tumor regression was linked to blockage of tumor evasion of the immune system and activation of T cell-mediated tumor destruction, as indicated by significant increase in CD4, CD8, CD45RO, CIITA, IL2, MHCI and MHCII expression with concomitant decrease in CD68 expression compared to the TM group. In addition, SCS relatively modulated tumor cell migration, invasion and angiogenesis, through downregulation of MMP9, MUC1 and VEGF in comparison with the TM group. Additionally, TM-S showed significant increase in E-cadherin expression with resultant decrease in N-cadherin, vimentin and Twist expression SCS. In general, these results demonstrate for the first time that SCS induced antimetastasis and immune system activation effects as part of its anticancer mechanism in 4T1-induced mouse mammary tumor model, and SCS-related bioactive constituents, especially lutein could perhaps contribute significantly to the anticancer potential of SCS.